Drug related medical emergencies in the elderly: role of adverse drug reactions and non-compliance. Issue 913 (1st November 2001) - Malhotra, S; Karan, R S; Pandhi, P; Jain, S
Abstract : BACKGROUND: Adverse drug reactions and non-compliance are important causes of admissions in the elderly to medical clinics. The contribution of adverse drug reactions and non-compliance to admission by the medical emergency department was analysed. METHODS: A total of 578 consecutive elderly patients admitted to the medical emergency department were interviewed to determine the percentage of admissions due to adverse drug reactions or non-compliance with medication regimens, their causes, consequences, and predictors. RESULTS: Eighty three (14.4%) of the 578 admissions were drug related: 39 (6.7%) caused by adverse drug reactions and 44 (7.6%) caused by non-compliance with medication. One hundred ninety two (33.2%) patients had a history of non-compliance. Factors associated with an increased risk of admission because of an adverse drug reaction were patients with diabetes or neoplasms, and patients using numerous different medications. Factors associated with a higher risk of hospitalisation because of non-compliance were poor recall of the medication regimen, seeing numerous physicians, female sex, polypharmacy, drug costs, and switching over to non-conventional forms of treatment. CONCLUSION: Many elderly admissions are drug related, with non-compliance accounting for a substantial fraction of these. Elderly people at high risk of suffering a drug related medical emergency are identified and suitable interventions may be planned by the healthcare policymakers to target them.